Destabilization of human cell genome under the combined effect of radiation and ascorbic acid - Domina, E.A.; Pylypchuk, O.P.; Mikhailenko, V.M. (Experimental Oncology, 2014)
The aim of this study was to investigate peculiarities of ascorbic acid effect on radiation-induced chromosomal aberrations frequency and range in the cultured peripheral blood lymphocytes (PBL) of healthy donors and cancer patients depending on doses of radiation and drug, as well as cells radiosensitivity (in vitro). Methods: Test system of human PBL, metaphase analysis of chromosomal aberrations. Cells were cultivated according to the standard procedures with some modifications. PBL culture was exposed to x-ray radiation in G0- and G2-phases of cell cycle. Immediately after the irradiation the culture was treated with ascorbic acid in concentrations of 20.0–80.0 µg/ml of blood. Results: Cell culture irradiation in low dose (0.3 Gy) and treatment with ascorbic acid in therapeutic concentration (20.0 μg/ml of blood) resulted in radioprotective effect, decreasing overall chromosome aberrations frequency as opposed to radiation effects. It has been established that post-irradiation effect of ascorbic acid upon the PBL culture in concentrations of 40.0 and 80.0 μg/ml, which exceeding therapeutic concentration value 2 and 4 times correspondingly, increased overall chromosome aberrations frequency 1.4 times compared with irradiation effect in a low dose (0.3 Gy). This bears evidence of ascorbic acid co-mutagenic activity in the range of concentrations exceeding therapeutic values. The peak of mitotic activity inhibition was observed at 2.0 Gy irradiation dose. Addition ascorbic acid in therapeutic concentration increased radiation effect this number ≈ 2 times (exceeding even intact control value). Compared with G0-phase, co-mutagenic effect of ascorbic acid in G2-phase appears earlier, starting with dose of 1.0 Gy. In the blood lymphocytes of cancer patients, the level of genetic damage was increased 1.7 times after combined treatment with low dose irradiation and ascorbic acid in comparison with irradiation alone which suggest the co-mutagenic instead of radioprotective effect of ascorbic acid. Conclusions: Genome destabilization enhancement of irradiated in vitro human somatic cells under ascorbic acid effect is due to its co-mutagenic properties. The formation of co-mutagenic effects of ascorbic acid depend on its concentration, irradiation dose and the efficiency of repair processes. Co-mutagenes may pose high carcinogenic hazard at low (above background) radiation levels. Key Words: ionizing radiation, ascorbic acid, peripheral blood lymphocytes of donors and cancer patients, chromosome aberrations, co-mutagens.